О нахождении садовой сони (Eliomys quercinus L.) на территории Ровенской области - Макарчук, П.Е. (Вестник зоологии, 1973)
Six individuals of Eliomys quercinus L. were found for the first time iii 1g65-1967 in Rovno region, Ukrainian SSR (in suburbs of villages Glinnoe and Khmel). The dates, when these animals were caught, are presented as well as their sex, age and size.